Assessment of Regional Groundwater Quality Based on Health Risk in Xi’an Region, P.R. China - Duan, Lei; Sun, Ya-Qiao; Wang, Wen-Ke (Asian Journal of Chemistry, 2014)
To reveal the relationship between the dynamic change of groundwater quality and human health, this paper uses the shallow groundwater in Xi’an region as the research object, introduces the health risk assessment into the dynamic study of regional groundwater and finally implements a dynamic assessment of the health risk associated with regional groundwater. The results show that the primary carcinogen in the shallow groundwater of Xi’an region is arsenic, with a carcinogenic risk exceeding the standard rate by 26.3 %. The primary non-carcinogenic chronic toxicity is nitrate, with a 50.66 % non-carcinogenic toxicity risk among the total non-carcinogenic risks. Besides, even for the groundwater satisfying the national standards for drinking water, its arsenic and nitrate pose potential risks for human health. There are generally declining tendencies for both the carcinogenic risk and the non-carcinogenic chronically toxic risk caused by toxic substances in groundwater, with exceptions for certain substances which still exceed maximum acceptable values recommended by US EPA. Therefore, it is extremely necessary for long-term observations and health risk management, especially in those high-risk regions with poorer groundwater quality. In that way, the adverse influences by chemical substances in the groundwater will be reduced for the health of drinking populations.